Uji Stabilitas Fisik dan Kadar Flavonoid Total Sediaan Gel Ekstrak Mesokarp Buah Semangka (Citrullus lanatus) - Indri Kusuma Dewi; Nur Atikah; Nabila Putri (Fakultas Farmasi Universitas Pancasila, 2022)
The content of flavonoids in the white skin or mesocarp of watermelon has antioxidant power so that the active substance can be used in the manufacture of cosmetics, one of which is a gel dosage form. This type of research is observational with a descriptive research design. The purpose of this study was to obtain data on the stability of the watermelon (Citrullus lanatus) mesocarp extract gel preparation using the cycling test method. Physical stability evaluations were carried out, including organoleptic, homogeneity, pH, adhesion, spreadability, and viscosity. The results showed that the organoleptic observation of the preparation was in the form of a semi-solid, had a characteristic aromatic odor of the extract, and had a brownish-yellow color. As for the test results for the entire homogeneous cycle, the average pH range is 4.75 - 5, adhesion is 2.45 - 3.96 seconds, dispersion is 5.59 - 6.67 cm, and viscosity is 5426 - 6830 cps, and total flavonoid content of the gel preparation was 5.27%. This study concluded that the gel preparation was physically stable before and after 12 days of storage and contained 5.27% flavonoids.